2002
DOI: 10.1073/pnas.122131099
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of human NOD/SCID-repopulating cells with both lymphoid and myeloid potential by foamy virus vectors

Abstract: The efficiency of gene transfer into human hematopoietic stem cells by oncoretroviral vectors is too low for effective gene therapy of most hematologic diseases. Retroviral vectors based on the nonpathogenic foamy viruses (FV) are an alternative gene-transfer system. In this study, human umbilical cord blood CD34 ؉ cells were transduced with FV vectors by a single 10-h exposure to vector stocks and then injected into sublethally irradiated nonobese diabetic-severe combined immunodeficiency (NOD͞SCID) mice. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 46 publications
3
70
0
5
Order By: Relevance
“…20 Vectors developed from foamy virus (FV), the only member of the Spumaretrovirinae subfamily of retroviruses, have an integration profile that is potentially safer than other retroviral vectors. [20][21][22][23][24] FV vectors have a reduced preference for integration within CpG islands known to be DNA regulatory regions and near promoters compared with GV vectors, and a reduced likelihood to integrate within genes relative to lentiviral (LV) vectors. 20,21 In addition to a more desirable integration profile, FV vectors also have a lower propensity to dysregulate nearby genes when directly compared with GV and LV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…20 Vectors developed from foamy virus (FV), the only member of the Spumaretrovirinae subfamily of retroviruses, have an integration profile that is potentially safer than other retroviral vectors. [20][21][22][23][24] FV vectors have a reduced preference for integration within CpG islands known to be DNA regulatory regions and near promoters compared with GV vectors, and a reduced likelihood to integrate within genes relative to lentiviral (LV) vectors. 20,21 In addition to a more desirable integration profile, FV vectors also have a lower propensity to dysregulate nearby genes when directly compared with GV and LV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The marking of human SCID-repopulating cells with FV vectors without in vivo selection or administration of cytokines has been demonstrated by our group and others [21][22][23]. High levels of FV marking in human cells may be due in part to the rapid expansion of the SCID-repopulating cells in the BM following homing and engraftment in the bone marrow of NOD/SCID mice.…”
Section: Discussionmentioning
confidence: 76%
“…Russell and colleagues demonstrated that murine stem cells residing in 5-fluorouracil (5FU)-treated bone marrow (BM) [24] and SCID-repopulating cells derived from umbilical cord blood and G-CSF-mobilized peripheral blood could be marked with FV vectors. [21,22] We previously demonstrated similar levels of gene marking using FV or lentiviral vectors to transduce SCID-repopulating cells derived from human umbilical cord blood CD34 + cells [23]. In addition, FV-mediated gene transfer of canine hematopoietic longterm repopulating cells has been recently reported [32].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 Novel retroviral vectors based on primate-and nonprimate foamy viruses (FV) which constitute the Spumavirinae subfamily of the retroviruses have currently been established and intensively examined by us and others. [3][4][5][6][7][8][9][10][11][12][13] For instance, FV vectors based on the human/primate FV allow efficient, stable and long-term transduction of human haematopoietic cells without detectable side effects. 11,12 FVs are considered to be apathogenic in their natural animal hosts and after zoonotic transmission into humans.…”
Section: Introductionmentioning
confidence: 99%